Extraordinary NO2 Removal by the Metal–Organic Framework UiO‐66‐NH2. Issue 21 (13th April 2016) - Peterson, Gregory W.; Mahle, John J.; DeCoste, Jared B.; Gordon, Wesley O.; Rossin, Joseph A.
Abstract: Here we discuss the removal of nitrogen dioxide, an important toxic industrial chemical and pollutant, from air using the MOF UiO‐66‐NH2 . The amine group is found to substantially aid in the removal, resulting in unprecedented removal capacities upwards of 1.4 g of NO2 /g of MOF. Furthermore, whereas NO2 typically generates substantial quantities of NO on sorbents, the amount generated by UiO‐66‐NH2 is significantly reduced. Of particular significance is the formation of a diazonium ion on the aromatic ring of the MOF, and the potential reduction of NO2 to molecular nitrogen. Abstract : Clean air with MOF : The metal–organic framework UiO‐66‐NH2 was used to remove toxic nitrogen dioxide from streams of air with only small amounts of nitric oxide formed. The highly efficient reaction was due to formation of several nitrate species, as well as a diazonium ion on the MOF secondary building unit. It is also possible that molecular nitrogen was formed during the reaction.